Game Transfer Phenomena and Problematic Interactive Media Use: Dispositional and Media Habit Factors - Ortiz de Gortari, Angelica B.; Gackenbach, Jayne (Frontiers in Psychology, 2021)
The study of the effects of interactive media has mainly focused on dysregulated behaviors, the conceptualization of which is supported by the paradigms of addiction. Research into Game Transfer Phenomena (GTP) examines the interplay between video game features, events while playing, and the manipulation of hardware, which can lead to sensory-perceptual and cognitive intrusions (e.g., hallucinations and recurrent thoughts) and self-agency transient changes (e.g., automatic behaviors) related to the game. GTP, in contrast to gaming disorder, are relatively common, not necessarily negative, and can influence the interpretation of stimuli and everyday interactions, although some gamers have reported feeling distress due to their GTP. This study investigates GTP and two forms of problematic interactive media (problematic video game playing (PVG) and problematic social media use (PSMU)) and focuses on dispositional and interactive media habit factors. A sample of 343 university students who played video games completed an online survey (58.7% male, 19–25 years old). Not all who had experienced GTP were identified as exhibiting PVG or PSMU, but all of those in the PVG group had experienced GTP. Overall, the profiles of the groups, including GTP (91.4%), PVG (28.5%), and PSMU (24.8%), were in accordance with previous findings. Those in the GTP and the PVG groups were characterized by being male, being highly engaged in the game (either while playing or via game-related activities) and having playing preferences. However, while those in the GTP group were significantly more likely to use YouTube and be fantasy prone, those with PVG were the ones that played most per day. Those in the PSMU group were characterized by being female and/or extroverted, frequently using social/sharing platforms, and seldom playing video games. A binary logistic regression revealed that the susceptibility to PVG among males was the strongest predictor of experiencing GTP, with fantasy proneness and engagement while playing also emerging as predictors. Future work can benefit from considering the role of GTP in gaming disorder, since intrusive thoughts, cognitive biases, and poor impulse control are pivotal in the initiation and maintenance of dysfunctional playing behaviors.